1965
DOI: 10.4319/lo.1965.10.suppl2.r25
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon in the Pacific and Indian Oceans and Its Relation to Deep Water Movements1

Abstract: Since 1948, carbon‐14 measurements on the bicarbonate of ocean water samples from the Pacific and Indian oceans have been carried out at the Scripps Institution of Oceanography, La Jolla, California. Previous reports of the results of these investigations have been confirmed and amended by many recent measurements. The method of extracting CO2 from ocean water has been modified and perfected over the past years. The most notable results of the measurements concern the 14C content of deep ocean water which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 1 publication
1
36
0
Order By: Relevance
“…In an accompanying paper , we discuss the shallow distribution of radiocarbon restrict our comments here to the deeper features. As was known from the earliest observations (Bien et al, 1960;Bien et al, 1965), the deep distribution of ∆ 14 C in the Pacific is dominated by a mid-depth (2000-3000 m) minimum. This minimum results from the incursion below 4000 m in the west of younger, higher ∆ 14 C waters ultimately derived from Antarctic Bottom and North Atlantic Deep Waters (Ostlund and Stuiver, 1980;Schlitzer, 2007).…”
mentioning
confidence: 96%
“…In an accompanying paper , we discuss the shallow distribution of radiocarbon restrict our comments here to the deeper features. As was known from the earliest observations (Bien et al, 1960;Bien et al, 1965), the deep distribution of ∆ 14 C in the Pacific is dominated by a mid-depth (2000-3000 m) minimum. This minimum results from the incursion below 4000 m in the west of younger, higher ∆ 14 C waters ultimately derived from Antarctic Bottom and North Atlantic Deep Waters (Ostlund and Stuiver, 1980;Schlitzer, 2007).…”
mentioning
confidence: 96%
“…Since that time there has been some controversy over the concentrations of these gases in the ocean. In general, the results of Mazor et al (1964), Konig et al (1964), andCraig et al (1967) suggest that the rare gases show only minor deviations from solubility equilibrium with the atmosphere while the data of Bieri et al (1964Bieri et al ( , 1966Bieri et al ( , 1968 and Hintenberger et al (1964) show larger variations and systematic departures from solubility equilibrium. Konig et al (1964) used volumetric techniques to determine nitrogen, argon, neon, and helium in Pacific and Indian Ocean waters.…”
Section: Nitrogen and The Rare Gasesmentioning
confidence: 83%
“…In 1964, the first measurements of rare gases (with the exception of argon) in the Ocean were reported independently by Konig et al (1964), Mazor et al ( 1964), and Bieri et al (1964). Since that time there has been some controversy over the concentrations of these gases in the ocean.…”
Section: Nitrogen and The Rare Gasesmentioning
confidence: 94%
“…Fig. 4 shows our effective profile superimposed on tracings of observed profiles in the Pacific and Indian Oceans by Bien et al (1965) and ranges of activity in various depth zones in the Atlantic from the data of Broecker et al (1960).…”
Section: A 14cmentioning
confidence: 99%
“…Bien and Suess (1967) extrapolated from samples of comparable depth profiles of 14C activity over time and concluded that as of the mid1960s weapons I4C had not penetrated significantly below 200 m in the waters of the Pacific. For our calibration we extended this hypothesis to all oceans and selected only those samples taken at depths equal to or greater than 200 m reported by Bien et al (1965) for the Pacific and Indian Oceans, and by Broecker et al (1960) for the Atlantic. More recent data have been deliberately excluded in view of evidence of deeper incursion of the weapons I4C (Stuiver and Ostlund, 1980;Ostlund and Stuiver, 1980).…”
Section: A 14cmentioning
confidence: 99%